2009
DOI: 10.1167/iovs.08-2595
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Visual Sensitivity in Retinal Prosthesis Patients

Abstract: PURPOSE With the long-term goal of restoring functional vision in patients with retinal degenerative diseases, the eyes of blind human subjects were implanted chronically with epiretinal prostheses consisting of two-dimensional electrode arrays that directly stimulated cells of the neural retina. METHODS Psychophysical techniques were used to measure the brightness of electrically generated percepts on single electrodes using a variety of electrical stimulation patterns. RESULTS It was possible to predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
137
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(147 citation statements)
references
References 55 publications
(74 reference statements)
4
137
0
6
Order By: Relevance
“…Although the results of Horsager et al (2009) in conjunction with our findings suggest that higher rates of spiking are associated with lower thresholds, it is important to point out that uniform delivery of high-rate pulse trains may not be the optimum stimulation strategy. Different types of ganglion cells each typically respond to visual stimuli with different spike frequencies (DeVries and Baylor 1997;Roska and Werblin 2001), and therefore it is probably not desirable to generate similar rates of high-frequency spiking in all types.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Although the results of Horsager et al (2009) in conjunction with our findings suggest that higher rates of spiking are associated with lower thresholds, it is important to point out that uniform delivery of high-rate pulse trains may not be the optimum stimulation strategy. Different types of ganglion cells each typically respond to visual stimuli with different spike frequencies (DeVries and Baylor 1997;Roska and Werblin 2001), and therefore it is probably not desirable to generate similar rates of high-frequency spiking in all types.…”
Section: Discussionsupporting
confidence: 51%
“…For example, Horsager et al (2009) found that the thresholds for eliciting percepts decreased as the rate of stimulation was increased. Presumably, changes in the rate of stimulation alter the rate at which spikes are elicited in targeted ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread morphological changes in the retina, various studies have shown the ability of ganglion cells in RD models to preserve their intrinsic firing properties (Jensen and Rizzo 2008;Margolis et al 2008;Stasheff 2008). Other investigations have exhibited the capability of higher order centers of visual processing to respond to electrical stimulation in such RD animal models (DeMarco et al 2007;Chan et al 2008) and also in clinical trials of retinal prosthesis (Caspi et al 2009;Horsager et al 2009). Furthermore, some studies have shown the preservation of ganglion cell morphology (Mazzoni et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, a variety of psychophysical [19][20][21][22][23][24] and retinal [25] data, as well as the potential distortions described in this review, suggest that this 'linear scoreboard' model is inadequate as an encoding model. To take the development of cochlear implant technology as a guide, a combination of psychophysical and neurophysiological research has led to dramatic improvements in cochlear implant coding schemes over the years.…”
Section: The Encoding Problemmentioning
confidence: 91%